Understanding and managing discolouration risk in trunk mains. (15th December 2016) - Husband, S.; Boxall, J.
Abstract: There is currently no accepted concept or approach for understanding and controlling discolouration risk associated with trunk mains. This paper assesses the applicability of cohesive layer theories to manage discolouration and a steady state empirical modelling tool that describes the process of particulate material accumulation. Results are presented from independent field experiments across the UK and internationally that evidence hydraulically induced mobilisation, or effectively cleaning, once imposed system shear stress exceeds normal conditions. Model calibration to measured data validates the cohesive layer concept with transferability in empirically derived parameters demonstrating a viable operational planning tool. The experiments highlight the accumulation of material layers as a continuous and ubiquitous process, such that fully clean pipes can never exist and helping explain how discolouration risk changes over time. A major practical implication of the novel understanding demonstrated in this paper is that discolouration risk in trunk mains can be simply managed by pro-active strategies that regularly vary the hydraulic conditions. This avoids the need for disruptive and expensive out of service invasive interventions yet offers operators a cost-effective long-term strategy to safeguard water quality. Graphical abstract: Highlights: Cohesive layer concept is validated as primary discolouration process in trunk mains. Material mobilisation shown to be a scalar property of system shear stress. Accurate and consistent model simulation of measured data supports layer concept. International transfer of PODDS model indicates ubiquitous worldwide process. Managed increases in flow can effectively and efficiently reduce discolouration risk.